Systematic Literature Review: Pemanfaatan Teknologi Disruptif Sebagai Upaya Transformasi Digital di Sektor Pemasaran - Ady Setiawan; Agus Purbo Widodo (Pusat Riset dan Inovasi Nasional, 2025)
The fourth industrial revolution encourages the use of disruptive technology in a variety of industries, including marketing. The study's goal is to investigate the potential, driving and hindering factors, as well as the impact of implementing disruptive technologies such as artificial intelligence (AI), big data, blockchain, and the internet of things (IoT) in the marketing industry. This study used the Systematic Literature Review (SLR) method with the Population, Intervention, Comparison, and Outcome (PICO) approach, as well as the Preferred Reporting Items for Systematic Reviews and Meta Analyses method, on literature or articles published between 2021 and 2025 that are relevant to the research title. According to the findings of the research, disruptive technology has a high potential for improving the effectiveness and efficiency of marketing operational activities, as well as producing more individualized consumer services. However, resistance to technology use, limits in digital infrastructure, and privacy or data security concerns continue to be major barriers to the introduction of disruptive technologies. The findings of this study highlight the importance of companies being prepared in terms of human resources and technology so that the implementation of disruptive technology can best assist the company and help the company achieve a competitive advantage in the increasingly dynamic digital market.